Cognitive Style and Information Visualization—Modeling Users Through Eye Gaze Data - Steichen, Ben; Fu, Bo (Frontiers in Computer Science, 2020)
Information Visualizations can be regarded as one of the most powerful cognitive tools to significantly amplify human cognition. However, traditional Information Visualization systems have been designed in a manner that does not consider individual user differences, even though human cognitive abilities and styles have been shown to differ significantly. In order to address this research gap, novel adaptive systems need to be developed that are able to 1) infer individual user characteristics, and 2) provide an adaptation mechanism to personalize the system to the inferred characteristic. This paper presents a first step towards this goal by investigating the extent to which a user’s cognitive style can be inferred from their behavior with an Information Visualization system. In particular, this paper presents a series of experiments that utilize features calculated from user eye gaze data in order to infer a user’s cognitive style. Several different data and feature sets are presented, and results overall show that a user’s eye gaze data can be used successfully to infer a user’s cognitive style during information visualization usage.